ТЕХНОЛОГИИ WEB 2.0 КАК УСЛОВИЕ ФОРМИРОВАНИЯ НАУЧНО – МЕТОДИЧЕСКОЙ WEB-ДЕЯТЕЛЬНОСТИ ПРЕПОДАВАТЕЛЯ - Рысюкова, Ю.В. (SCIENCE and SOCIETY, 2018)
The author of the article describes the process of formation and development of scientific-methodological web activities of a modern University teacher, the principal bases of which are web 2.0 technologies. There is a comparative analysis of web 1.0 and web 2.0. The author of the article also outlines the advantages of implementation of scientific-methodical web-activities.